2015
DOI: 10.1002/ajoc.201500495
|View full text |Cite
|
Sign up to set email alerts
|

Metal‐Free C(sp3)‐O Bond Formation through Radical Translocation: A Mild, Efficient, and Practical Approach to α‐Alkoxybenzamides

Abstract: Am ild and metal-free method to functionalize aliphatic CÀHb onds adjacent to an itrogen atom through radical translocation, oxidation to an iminium intermediate, and nucleophilic trapping with alcohols is described. The transformation proceeds efficiently with edible ascorbic acid (vitamin C) as the radical initiator andr eadily available tert-butyl nitrite as the nitrosating reagent. Notably,a ny transition-metal or additive is not required. The current methodp rovides simple, efficient, and practical access… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…Given the above mentioned control experiments and inspired by mechanistic investigations previously reported, we have proposed a plausible mechanism for this reaction (Scheme ). The fact that O ‐acetyl salicylic acid has a moderate positive impact on the reaction, while methyl salicylate does not act as catalyst suggested that the carboxylate is directly involved in the reaction.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Given the above mentioned control experiments and inspired by mechanistic investigations previously reported, we have proposed a plausible mechanism for this reaction (Scheme ). The fact that O ‐acetyl salicylic acid has a moderate positive impact on the reaction, while methyl salicylate does not act as catalyst suggested that the carboxylate is directly involved in the reaction.…”
Section: Resultsmentioning
confidence: 98%
“…Recently, Carrillo and co‐workers demonstrated that in‐situ generated arenediazonium ions can be conveniently reduced to aryl radicals at room temperature, using substoichiometric amounts of ascorbic acid (AscH 2 ) or gallic acid as promoters. The AscH 2 protocol has been implemented for the radical C−H arylation of (hetero)arenes in the preparation of aryl sulfides, in a [4+2] benzannulation to build phenanthrenes, and in a radical translocation to form α ‐alkoxybenzamides . However, to our surprise, the use of these promoters in a one‐pot reductive deamination of anilines has not been documented so far.…”
Section: Introductionmentioning
confidence: 99%
“…Trapping of such electrophilic iminies by a suitable nucleophile afforded the corresponding α-C–H functionalized products in good to moderate yields. In 2016, Zhang and Qi developed a metal-free approach for this reaction employing either ascorbic acid (vitamin C), or organic photocatalyst as the radical initiator. , …”
Section: Distal C(sp 3 )–H Functionalization Involving Radically Ini...mentioning
confidence: 99%
“…In 2016, Zhang and Qi developed a metal-free approach for this reaction employing either ascorbic acid (vitamin C), or organic photocatalyst as the radical initiator. 593,594 In 2016, Maulide and co-workers described a metal-free, redox neutral method for the α-C−H amination followed by ring opening of cyclic amines, leading to acyclic products (Scheme 288). 595 The reaction proceeded with the generation of transient aryl radical.…”
Section: Pyridinementioning
confidence: 99%
“…In 2016, the Zhang and Qi groups developed metalfree versions of this transformation using ascorbic acid as the radical initiator, or organic photocatalysts. 156,157 Additionally, the hemiaminal products were treated with a Lewis acid and either allylSiMe 3 or Me 3 SiCN to afford a net C-H α-allylation or α-cyanation. Alternatively, Maulide and co-workers employed a hydrazine that serves two roles: reductant to generate the aryl radical, and nucleophile for addition into the transient iminium formed upon α-amino radical oxidation.…”
Section: Review Syn Thesis Scheme 26 C-h Alkylation Of α-Amines and αmentioning
confidence: 99%